Quantitative Study of the Effect of Progesterone on the Diabetic Sural Nerves in Rats - Altaf, Faris M (Pakistan Journal of Nutrition, 2017)
Objective: The quantitative effects of progesterone injection on the diabetic peripheral nerves with peripheral neuropathy was studied in this experiment. Methodology: Forty two-months-old male albino rats were used in the present study (4 animals as normal control). Diabetes was inducted in 36 animals by a single intravenous injection of freshly prepared streptozotocin (STZ) (65 mg kg–1, Sigma, Milano, Italy) in citrate buffer 0.09 M, pH 4.8 in each animal. The diabetic animals were divided into two groups (18 diabetic control and 18 received 16 times of injection of progesterone). All the specimens were processed for light microscopic study and were photographed at 40X than at 100X. The obtained photographs were studied using the image analyzing system. The myelinated nerve fibers were studied quantitatively (diameters of nerve fibers and axons, surface areas, number and myelin thickness). The obtained values were statistical analyzed using t-test and were compared. Results: There were significant increase in the diameters of nerve fibers and axons, surface areas, number and myelin thickness in the myelinated diabetic nerves treated with progesterone than that of the diabetic control. The diabetic nerves showed significant decrease in the above parameters compared to the normal control. Conclusion: Progesterone injection has neuroprotective properties and can ameliorate the structural changes in the diabetic nerves.